2012
DOI: 10.1113/jphysiol.2012.237834
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia–reoxygenation‐induced endothelial barrier failure: role of RhoA, Rac1 and myosin light chain kinase

Abstract: Key points• Hypoxia-reoxygenation induces loss of endothelial barrier function and oedema formation accompanied by a rise in intracellular Ca 2+ , an increase in myosin light chain (MLC) phosphorylation, and RhoA/Rho kinase (Rock) signalling and an inactivation of Rac1.• Neither inhibition of RhoA/Rock signalling nor antagonising Ca 2+ increase could protect against this hypoxia-reoxygenation-induced loss of barrier function.• Inhibition of MLC kinase (MLCK) abrogates hypoxia-reoxygenation-induced MLC phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 32 publications
4
43
0
4
Order By: Relevance
“…Interestingly it has been shown in different cell types that hypoxia influences members of the Rho family of GTPases [10][14], which are master regulators of the actin cytoskeleton [15], [16]. Besides cell motility the actin cytoskeleton governs many other cellular activities like cytokinesis, endocytosis, cell adhesion and cell shape [17][20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly it has been shown in different cell types that hypoxia influences members of the Rho family of GTPases [10][14], which are master regulators of the actin cytoskeleton [15], [16]. Besides cell motility the actin cytoskeleton governs many other cellular activities like cytokinesis, endocytosis, cell adhesion and cell shape [17][20].…”
Section: Introductionmentioning
confidence: 99%
“…65 The endothelial barrier function is made up by the glycocalyx, 66 endothelial cells, and pericytes (particularly at the postcapillary venules 67 ). Endothelial cytoskeletal derangement and hypercontracture induce gap formation, [68][69][70][71] which is enhanced by extracellular adenosine but attenuated by extracellular ATP. 72 Degradation of the glycocalyx also contributes to reduced endothelial barrier function and edema formation 66,73,74 ; tumor necrosis factor α is an important mediator of glycocalyx degradation, 75 and glycocalyx degradation also promotes leukocyte 76 and platelet adherence.…”
Section: Vascular Permeability: Edemamentioning
confidence: 99%
“…Upon activation, HIF-1α regulates a wide range of genes involved in many cellular processes such as angiogenesis, glycolytic energy metabolism, oxygen delivery, cell proliferation, and survival, which collectively lead to the adaptive response of cells and tissues [10,11,12,13,14]. Previous reports have shown that the expression of HIF-1α protein is remarkably increased in endothelial cells exposed to hypoxia [15,30,31]. In accordance with the data from these previous studies, our present study demonstrates that hypoxia treatment induced a significantly increased protein expression of HIF-1α and GLUT-1, an HIF-1 target gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that HIF-1α is involved in barrier dysfunction by inducing the expression of HIF-1 target genes such as vascular endothelial growth factor, inducible nitric oxide synthase [38,40,46], aquaporin-4, matrix metalloproteinase-9 [39], macrophage migration inhibitory factor [47], as well as by repressing the expression of vasodilator-stimulated phosphoprotein [48]. However, the activation of MLCK, which in turn leads to an increase of MLC phosphorylation, has been reported to play a critical role in endothelial and intestinal barrier dysfunction induced by hypoxia or inflammation [21,22,23,24,28,29,31,49]. In addition, our previous studies have revealed that HIF-1α-dependent up-regulation of MLCK protein is involved in barrier dysfunction induced by hypoxia or proinflammatory cytokines [15,25,26].…”
Section: Discussionmentioning
confidence: 99%